Biopolimer Preparation of Cellulose Nanowhiskers from Oil Palm Empty Fruit Bunches (Elaeis guineensis Jacq.) as a Biopolymer Composite Material - Minda Yani; Melfa Aisyah Hutasuhut; Leni Widiarti (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to develop cellulose nanowhiskers from oil palm empty fruit bunches (Elaeis guineensis Jacq.) as an environmentally friendly reinforcing material for biopolymer composites and to evaluate their characteristics using FTIR, TEM, XRD, and DSC analyses. This development was intended to produce composite materials with improved mechanical properties and thermal stability, thereby offering potential applications in eco-friendly products such as biodegradable packaging, lightweight automotive materials, and biopolymer-based construction materials. The fabrication process involved several sequential stages, including alkaline pretreatment using NaOH, bleaching with NaOCl, cellulose isolation, acid hydrolysis using H₂SO₄, and subsequent mechanical refinement using a ball mill. The yield calculation showed a value of 3.33% based on the initial raw material weight. TEM observations indicated that the cellulose nanowhiskers exhibited a varied particle size distribution, with particles in the range of 50–100 nm tending to be more uniform than larger particles. XRD analysis revealed a crystallinity index of 54.50% and a characteristic cellulose I pattern, indicating that most of the structure was present in crystalline form. DSC analysis further demonstrated that the cellulose nanowhiskers possessed good thermal stability. Based on these findings, cellulose nanowhiskers derived from oil palm empty fruit bunches show considerable potential as environmentally friendly reinforcing agents for biopolymer composites.